Wastewater Treatment with Polymeric Membranes - Andreea Liliana LAZĂR; Iulian Gabriel BÎRSAN (ACROSS)
Membrane processes for industrial wastewater treatment are used for large types of pollutants in the pharmaceutical industry, textile industry, food industry, agronomy, but it also has the disadvantage of fouling which has an influence on the water flow. To minimize these problems, it is necessary to obtain membranes with a reduced roughness, so we will also obtain an increase in water flow. By increasing the polymer concentration, the membrane has lower porosity and the water flow decreases. The roughness increases at a lower concentration of polymer because the pours are connected with the surface and the top layer disappears. Research in the field has shown the improvement of membrane properties by adding additives, but these represent additional costs of the process. In this paper, results of the properties of membranes obtained at different concentrations and thicknesses of the polymer are presented. 1-Methyl-2-pirrolidinone (NMP) solvent and polyethersulfone (PES) polymer were used to make the membranes. Polyethersulfone membranes were fabricated using phase inversion. The results show that the polymer concentration has an important influence on the water flux. In this study, there are presented four types of membranes with concentrations ranging from 15 wt.% – 30 wt.% and two different types of thicknesses, 200 μm and 300 μm. The thickness has a negative impact on the water flux. After the preparation of the membranes at different concentrations and thicknesses of the polymer, the flow of the membranes was determined, and after its establishment, the permeability of the membranes was determined. It has been observed that the permeability decreases when high concentrations of the pouring solution are used.